Características fermentativas e nutricionais de silagens compostas por palma forrageira e gliricídia - Brito, Gêsica Samíramys Mayra da Silva (2018)
The use of conserved forage is a good alternative to minimize the effects of seasonality on forage production, mainly in semiarid regions. There are many plants which could be used in silage making, but the cactus is highlighted for having high biomass production and high soluble carbohydrate content. Despite of this, the protein, fiber and dry matter content of this plant is low making it unsuitable as exclusive forage to silage production and for feeding ruminants. Thus, it is reasonable to consider the addition of a protein and fiber source in the ensiling process, as the forage legume, which would improve substantially the nutritional value of the mixed silages. Within all the forage legumes available, the gliricidia is more adapted to semiarid conditions and to complement the nutritional deficit of the cactus. The objective of this study was to evaluate the microbial populations, fermentation profile, fermentative losses, aerobic stability and the bromatological composition of cactus silages added of gliricidia in different levels. The material was collected in the EMBRAPA Semiárido, located in Petrolina-PE. The bromatological composition analysis was performed at this institution and in Forage Crop Laboratory at UFPB, Campus II, Areia-PB. The experiment was conducted according to a completely randomized design, with 3 replications, in a factorial scheme (5 x 6). The treatments consisted of five silages with different levels of gliricidia (0, 25, 50, 75 and 100%) and six periods of silos openings (1, 7, 15, 30, 60 and 90 days). For the aerobic stability test, it was used a 5 x 2 factorial scheme, with three replicates, evaluating five levels of gliricidia addition and two periods of air exposure (48 and 96 h). The data were submitted to analysis of variance and regression. The means in time were compared by t-test at 5% probability. There was interaction for treatment x opening period for the fermentation profile of the silages. All silages presented pH values with indicative of good fermentation (3.8 to 4.2), except for the inclusion level of 100% (pH 5.3). The production of ammoniacal nitrogen, on average, did not pass of 3.4% (total N%). The soluble carbohydrate content decreased after 90 days of the ensiling process. The buffer capacity increased as gliricidia was added, but without negative effect on the fermentation of the same. There was an effect to treatment x opening period for lactic acid (LA), acetic acid (AC), propionic acid (AP) and AL:AC, which were considered as desirable. The silages had minimal losses by gases (LG) and effluents (LE). The lowest LG were observed in the silages with 50% addition of gliricidia, while the lowest LE were observed in the silages with inclusion of 75 and 100% of gliricidia. It was verified and positive effect of inclusion of the gliricidia on the bromatological composition of the mixed silages, mainly in the dry matter, mineral matter, organic matter and ether extract contents. There was interaction of treatment x opening for crude protein, neutral detergent insoluble fiber, acid detergent insoluble fiber, lignin, hemicellulose, neutral detergent insoluble protein and neutral detergent insoluble ash, increasing according to the level of gliricidia inclusion. Gliricidia improves the nutritive value of cactus silages.